Halakhah in a Theological Perspective - Novak, David (Brown Judaic Studies, 2020)
This volume examines the ideas of Rabbi Moses ben Nahman (1194-1270), the Ramban, Nahmanides in the European literature. An exegete, epistemologist of Jewish history and experience, and pioneer of Kabbalistic reasoning, Nahmanides was the spokesperson of embattled Spanish Jewry at the ominous Barcelona disputation before King James of Aragon in 1263. Novak surveys the canon of Nahmanides' writings-commentaries, discourses, sermons, even the record made by the Ramban of his Barcelona disputation-to elicit the structure of a systematic theology. As Novak shows, he often subordinated perfect consistency to the nuances he discovered in a text. He willingly sacrificed the chance to enlarge some favorite speculative theme to the material message he found in tradition.